The Impact of Trade Openness on Indonesia's Economic Growth - Pratama Putra, Anggara; Liana, Damia; Lamin Conteh, Mohamed (Journal of Economics Development Issues, 2025)
Globalization has encouraged trade openness to support economic growth. The dynamics of Indonesia's economic growth in the last three decades have tended to fluctuate, especially during a crisis. Empirical studies on the impact of trade openness on Indonesia's economic growth show different results. Therefore, this study aims to examine the relationship between trade openness and Indonesia's economic growth, including when the crisis hit Indonesia. This study uses secondary data from 1984-2023 using ARDL method. The results shows that there is a positive and significant relationship between trade openness and Indonesia's economic growth in the long-term, but in the short-term trade openness has a negative impact on Indonesia's economic growth. In addition, human capital and FDI have a positive impact on Indonesia's economic growth in the long-term. The crisis that occurred will cause a decline in Indonesia's economic growth in the short-term, but the effect does not last in the long-term. Keywords: ARDL; Economic Growth; Trade Openness.